Enhanced steroid dosing reduces seizures during antiparasitic treatment for cysticercosis and early after. Issue 9 (4th August 2014) - Garcia, Hector H.; Gonzales, Isidro; Lescano, Andres G.; Bustos, Javier A.; Pretell, E. Javier; Saavedra, Herbert; Nash, Theodore E.; The Cysticercosis Working Group in Peru
Summary Objective Neurocysticercosis (NCC) is a major cause of seizures and epilepsy in endemic countries. Antiparasitic treatment of brain cysts leads to seizures due to the host's inflammatory reaction, requiring concomitant steroids. We hypothesized that increased steroid dosing will reduce treatment‐associated seizures. Methods Open‐label randomized trial comparing 6 mg/day dexamethasone for 10 days (conventional) with 8 mg/day for 28 days followed by a 2‐week taper (enhanced) in patients with NCC receiving albendazole. Follow‐up included active seizure surveillance and brain imaging. Study outcomes were seizure days and patients with seizures, both measured in days 11–42. Additional analyses compared days 1–10, 11–21, 22–32, 33–42, 43–60, and 61–180. Results Thirty‐two individuals were randomized into each study arm; two did not complete follow‐up. From days 11 to 42, 59 partial and 6 generalized seizure days occurred in 20 individuals, nonsignificantly fewer in the enhanced arm (12 vs. 49, p = 0.114). The numbers of patients with seizures in this period showed similar nonsignificant differences. In the enhanced steroid arm there were significantly fewer days and individuals with seizures during antiparasitic treatment (days 1–10: 4 vs. 17, p = 0.004, and 1 vs. 10, p = 0.003, number needed to treat [NNT] 4.6, relative risk [RR] 0.1013, 95% confidence interval [CI] 0.01–0.74) and early after dexamethasone cessation (days 11–21: 6 vs. 27, p = 0.014, and 4 vs. 12, p = 0.021, NNT 4.0, RR 0.33, 95% CI 0.12–0.92) but not after day 21. There were no significant differences in antiparasitic efficacy or relevant adverse events. Significance Increased dexamethasone dosing results in fewer seizures for the first 21 days during and early after antiparasitic treatment for viable parenchymal NCC but not during the first 11–42 days, which was the primary predetermined time of analysis.